Visitor Perception of the Agricultural Research and Assessment Installation (IP2TP) in Samboja Case Study: Visits by Students from the State Polytechnic of Samarinda - Ria Widyaningrum (Indonesian Journal of Social Responsibility Review (IJSRR), 2023)
The study aimed to investigate the perception of visitors towards the Agricultural Research and Assessment Installation (IP2TP) in Samboja, with a specific focus on visits by students from the State Polytechnic of Samarinda. IP2TP Samboja serves as a testing ground for various agricultural technological innovations developed by the Agricultural Research and Development Agency (Badan Penelitian dan Pengembangan Pertanian). Additionally, it provides a learning platform for agricultural students, allowing them to engage in fieldwork activities and gain firsthand knowledge of the innovative technologies employed. A descriptive analysis method was employed, utilizing surveys to collect data. The respondents consisted of 80 randomly selected students from the State Polytechnic of Samarinda (Politeknik Pertanian / Politani) who had participated in visits to IP2TP Samboja. The findings of the study indicated that visitor perception of IP2TP Samboja was influenced by factors such as the visitors' educational background and their level of interest in specific agricultural commodities.